Penerapan Permainan Outdoor Untuk Meningkatkan Kemampuan Jati Diri Anak - Asmaul Husna; Jusmaniar Kasim; Nurfadillah Fitria; Nurmayanti; A. Asrifatil Jannah (Ihya Ulum: Early Childhood Education Journal, 2023)
The early period of a child's life is a very important time in shaping the individual's identity. During this period of development, outdoor games provide opportunities for children to strengthen the concept of identity. The purpose of this study is to evaluate the extent to which the application of outdoor games can be effective in shaping children's identity skills. This study used experimental research (quasi-experiment) with a one-group pretest-posttest design. The sample of this study was selected using purposive sampling with criteria including students aged 5-6 years at Al-Furqan Kindergarten, Sapobonto Village, Bulukumpa District, Bulukumba Regency. Data collection techniques using observation sheets and data analysis using parametric inferential statistics that require data normality to test hypotheses, using paired sample t-test analysis. The results showed that outdoor game activities have a positive effect on improving the ability of students' identity, including their ability to improve gross motor skills, coordination and balance, social, cognitive, and self-confidence and courage.